Strategi Komunikasi Pemasaran Terpadu pada Pada Promosi Film Nanti Kita Cerita Tentang Hari Ini - Syifa Mutiara; Tantan Hermansyah; Nasichah Nasichah (CV. ITTC INDONESIA, 2023)
Film has developed into a medium of expression that has commercial value. Film also has the function of mass media, namely to entertain audiences or viewers. Behind the signs of progress and the current national film industry, there are still gaps and ups and downs in its growth. There are a number of problems that are still found in the film production process. To overcome this problem in the production of a film, a promotional strategy is needed to disseminate information widely regarding the publication of films that have been produced. The purpose of this study is to find out the integrated marketing communication strategy in the film